Pengaruh Kepemilikan Manajerial, Dewan Komisaris, Tipe Industri dan Umur Perusahaan Terhadap Sustainability Reporting - Anisa Anisa; Dirvi Surya Abbas; Hustna Dara Sarra (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the Effect of Managerial Ownership, Board of Commissioners, Type of Industry and Company Age on Sustainability Reporting on Non-Financial Companies Listed on the Indonesia Stock Exchange. This study uses a quantitative approach. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period. The sampling technique used purposive sampling technique and obtained a sample of 18 companies. The data analysis technique used is panel data regression analysis. The results of the study show that together the independent variables consisting of the influence of managerial ownership, the board of commissioners, industry type and company age have an effect on sustainability reporting.